Dehydration of biomass charcoal briquette using a modified solar tunnel drying system: An experimental and CFD approach - Dagim Kebede Gari; Venkata Ramayya Ancha; Yetenayet Bekele Tola (Case Studies in Thermal Engineering)
Biomass charcoal briquettes ensure sustainable energy, environment, and socio-economic development, which addresses the rapid growth of renewable energy demand. However, its adoption is low due to many challenges, especially the drying process. Thus, this study examines the dehydration of biomass charcoal briquettes using an active-mode, double air-pass solar tunnel dryer, aiming to improve both drying efficiency and economic feasibility. The drying performance parameters were analyzed using an experimental and computational fluid dynamics (CFD) approach. During the dehydration experiment, the average temperature of the drying unit, as well as its thermal and exergy efficiencies, were found to be 55.2°C, 56.8%, and 52.9% under loading conditions, while being 54.3°C, 54.1%, and 51.8%, respectively, under no-load conditions. The initial moisture content was found to be 45.31%, and the final moisture content was below 10% after drying for 5 – 6 hours in the modified dryer and 14 – 16 hours under open sun drying. The study reveals that the newly developed solar tunnel dryer enhances the thermal energy of water molecules as well as the rates of evaporation and diffusion, thereby increasing the moisture removal rate and reducing the drying period. This, in turn, increases the drying and economic feasibility.